Review of the genus Paragolsinda Breuning, 1956 (Coleoptera, Cerambycidae, Lamiinae, Mesosini), with reconsideration of the endophallic terminology - Yamasako, Junsuke; Ohbayashi, Nobuo (Zootaxa, 2011)
The genus Paragolsinda Breuning, 1956 is reviewed. To date, only the type species of the genus, P. fruhstorferi Breuning, 1956 has been known. Two species of the genus Mesoereis Matsushita, 1933, M. tonkinensis Breuning, 1938 and M. obscurus Matsushita, 1933, are transferred to the genus Paragolsinda by the features of external structure judged from the photographs of the type specimen of P. fruhstorferi. A new species, Paragolsinda siamensis sp. nov. from Northern Thailand, is described. The structures of endophallus except for the type species are described with illustrations. The terminology for the structure of endophallus employed in our previous paper is partly modified in accordance with recent references.